"Hotel backyard": hoteliers' perspectives on hotel suicides. Issue 1 (2nd January 2023) - Kırlar-Can, Burçin; Ertaş, Mehmet
ABSTRACT: This study investigates the perspectives of hotel employees and managers on hotel suicide based on the opportunity theory. Using an exploratory qualitative research design to gain insights into undesirable events in hotels, the study examines the opinions, attitudes, and management skills of hoteliers in preventing suicide and coping with the after-effects. Face-to-face in-depth interviews were conducted with sixteen hoteliers in Denizli, Türkiye. Data collection included scenarios consisting of newspaper articles about hotel suicide cases. The findings demonstrated that hotels mostly meet their legal obligations, such as taking registration, checking identity, and sending instant identity reports to the police station. However, they rarely take preventive measures against suicidal events.